Risk of hematological malignancies and anticipation in the families of patients with non-Hodgkin and Hodgkin lymphoma - Akhtar, Saad; Mushtaq, Ali Hassan; Syed, Huda; Elhassan, Tusneem Ahmed M.; Alzahrani, Meshari Jamaan; Rauf, M Shahzad; Elshenawy, Mahmoud A; Maghfoor, Irfan (Frontiers in Oncology, 2025)
ObjectivesData on patients with non-Hodgkin lymphoma (NHL) and Hodgkin lymphoma (HL) with a family history of malignancy (FHM) and anticipation are limited. These patients provide an opportunity to study the responsible genes and clinical outcomes. There is no comprehensive report from the Middle East, where large family sizes and consanguineous marriages are common. Here, we report our observations.MethodsThis was a retrospective, single-institution cohort study. Patients seen in the lymphoma clinics were comprehensively interviewed for FHM.ResultsWe interviewed 1,274 lymphoma patients for FHM: 591 (46.4%) with NHL and 683 (53.6%) with HL; 745 (58.5%) were men. The median age was 32 years. Consanguineous marriages were reported in 9.1% (parents) and 9.2% (patients). Among them, 524 (41.1%) patients had no FHM, whereas 750 (58.9%) had FHM. Patients reported a total of first-, second-, and third-degree relatives and 1,249 relatives with 1,263 malignancies. In total, 254 patients reported family members with hematological malignancy only (131, 10.3%) or hematological plus solid malignancies (123, 9.7%), while 496 (38.9%) reported only solid cancers. In total, 254 patients identified 305 affected relatives: NHL, 67 (22%); HL, 70 (23%); lymphoma not otherwise specified (NOS), 30 (9.8%); leukemia, 111 (36.4%); and other hematological malignancies, 27 (8.5%). Relationship pairs (n = 305) included parent/child (36), sibling/sibling (54), sibling/half-sibling (6), uncle/aunt or nephew/niece (46), grandparent/grandchild (14), and patient/cousin (59). These 305 disease pairs were: NHL/NHL, 39 (12.8%); NHL/lymphoma NOS, 17 (5.6%); NHL/HL, 66 (21.6%); NHL/leukemia, 47 (15.4%); NHL/others, 4 (1.3%); HL/HL, 51 (16.7%); HL/lymphoma NOS, 13 (4.3%); HL/leukemia, 64 (21%); and HL/others, 4 (1.3%). Anticipation data were available for 92 pairs (63.3%); earlier age at diagnosis in the first generation (58 years) versus the second generation (24 years, p=<no><</no> 0.001) was significant, even after correction for ascertainment bias.ConclusionIn patients with NHL and HL, FHM is common, and anticipation was observed. Future studies should explore the genetic basis of these findings.